STEEP ROAD TOWARDS REGULATING FOR SUCCESS OF IMPLEMENTATION OF RECLAMATION AND POST MINING OF MINERAL AND COAL - Barkatullah, Abdul Halim; Syaifudin, Syaifudin; Mahyuni, Mahyuni; Ifrani, Ifrani (Program magister Kenotariatan Fakultas Hukum Universitas Lambung Mangkurat, 2017)
Coal and Mineral mining activities have a high risk of ecosystem changesthat affect the environment, let alone the mining is carried out openly. In order torestore the condition of the land in such a way that it can function and to be effectivein line with its allocation, the ex-mining area must be restored. Reclamation andpost-mining activities shall be conducted by every holder of Mining Business Permit(IUP) Exploration and IUP Production. Holders of IUP Exploration must firstlyprepare reclamation and post-mining plans in the permit process. The implementationof reclamation and post-mining activities by holders of IUP Production Operationand Special Mining Business Permit (IUPK) Production Operation must complywith the principles of : (1)protection and management of mining environment; (2)working safety and health; and (3) mineral and coal conservation. To determinethe success of the land that has been reclaimed and the post-mining activities havebeen complied, if an evaluation has been made by the competent officials and it isstated that the reclamation and post-mining activitie shave been performed well in accordance with prevailing regulations.